1993
DOI: 10.1007/bf00479396
|View full text |Cite
|
Sign up to set email alerts
|

Phenols and nitrophenols as tropospheric pollutants: Emissions from automobile exhausts and phase transfer in the atmosphere

Abstract: Motor exhaust gas from an automobile motor, operated under stationary conditions with unleaded gasoline, was sampled with two different impinger bath methods. The samples were analyzed by gas chromatography /mass spectrometry (GC/MS) for phenol, cresols and nitrated phenols. Phenol and cresols were measured in the range of 80 -220 nmol/L of exhaust gas from a noncatalyst engine, and nitrated phenols were found in the range of 9 -36 nmol/L. A large reduction of total phenols down to 7% and less was observed whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
98
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(105 citation statements)
references
References 13 publications
6
98
0
1
Order By: Relevance
“…This source mainly comes from the heavily trafficked urban areas of Jinan and major roads near the Yucheng and Wangdu sites. The direct emission of nitrated phenols from car engines was confirmed in a laboratory study by Tremp et al (1993), which gave an emission factor of 9 to 36 nmol L −1 .…”
Section: Temporal and Spatial Variationsmentioning
confidence: 75%
See 1 more Smart Citation
“…This source mainly comes from the heavily trafficked urban areas of Jinan and major roads near the Yucheng and Wangdu sites. The direct emission of nitrated phenols from car engines was confirmed in a laboratory study by Tremp et al (1993), which gave an emission factor of 9 to 36 nmol L −1 .…”
Section: Temporal and Spatial Variationsmentioning
confidence: 75%
“…Due to the good correlation with levoglucosan, Iinuma et al (2010) pointed out that NCs could be a reasonable tracer for biomass burning events. In addition to biomass burning, other combustion activities (e.g., coal, gasoline) are possible sources of nitrated phenols (Nojima et al, 1983;Tremp et al, 1993;Yan et al, 2015); their contributions, however, have not yet been well evaluated. Furthermore, nitrated phenols have been used as pesticides in some farmlands and are widely used as raw materials in industrial processes (Harrison et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…This study explored the interference potential of three known types of automated exhaust aromatic atmospheric constituents: o-nitrophenol, naphthalene, and p-tolualdehyde. 32,33 Figure 2 shows the results of one test carried out in dry (Ͻ3% RH) air. The signals for the UV O 3 monitors are elevated at the start of the test because the chamber contained residual Hg from a test conducted earlier in the day.…”
Section: Effect Of Selected Chemicals On Omentioning
confidence: 99%
“…The problem is that the compounds most likely to interfere (polar oxygenated and nitrogenated derivatives of aromatic hydrocarbons) are rarely measured in the atmosphere so it is difficult to assess their potential cumulative interference. Tremp et al 32 have reported substantial primary emissions of phenols and nitrophenols from gasolinefueled motor vehicles, and these compounds are also known secondary products of photochemical oxidation in polluted atmospheres, so the potential for interference exists. The question is how serious the interference is during the hot, humid, stagnant design value-day conditions that often occur at a site providing the highest 3-yr average of the annual 4th highest daily maximum 8-hr average O 3 values used to determine attainment in regions nearing compliance with air quality regulations.…”
Section: Effect Of Selected Chemicals On Omentioning
confidence: 99%
“…11 Oxidation of phenols and cresols by OH/NO x and NO 3 radicals are mainly responsible for the secondary formation of different nitrophenols. [12][13][14] Nitrophenols have been detected in ambient air, 11,[15][16][17] clouds, 18 soil, 19 fog 20 and snow. 21 In contrast to the liquid phase, 11,[22][23][24] the photochemistry of nitrophenols in the gas phase has, to the best of our knowledge, received virtually no attention.…”
Section: Introductionmentioning
confidence: 99%